82 Spatiotemporal aed optimisation is generalizable. (16th April 2018) - Sun, CLF; Karlsson, L; Torp-Pedersen, C; Folke, F; Chan, TCY
Abstract : Aim: Mathematical optimisation of automated external defibrillator (AED) placements has the potential to improve out-of-hospital cardiac arrest (OHCA) coverage and reverse the negative effects of limited AED accessibility. However, the generalizability of optimisation approaches has not yet been investigated. Method: We examined the performance and generalizability of a spatiotemporal AED placement optimisation methodology, initially developed for Toronto, Canada, 1 to the new study setting of Copenhagen, Denmark. We identified all atraumatic treated public OHCAs (1994–2016) and all registered AEDs (2016) in Copenhagen, Denmark. We then calculated the coverage loss associated with limited temporal accessibility of registered AEDs, and used a spatiotemporal optimisation model to quantify the potential coverage gain of optimised AED deployment. Coverage gain of spatiotemporal deployment over a spatial-only solution was quantified through 10-fold cross-validation. Statistical testing was performed using χ2 and McNemar's tests. Results: We identified 2149 public OHCAs and 1573 registered AED locations. Coverage loss was found to be 24.4% (1, 104 OHCAs covered under assumed 24/7 coverage, and 835 OHCAs under actual coverage). The relative coverage gain from using the spatiotemporal model over a spatial-only approach was 15.3%. Temporal and geographical trends in coverage gain were similar to Toronto. Conclusion: Without modification, a previously developed spatiotemporal AED optimisation approach was applied to Copenhagen, resulting in similar OHCA coverage findings as Toronto, despite large geographic and cultural differences between the two cities. In addition to reinforcing the importance of temporal accessibility of AEDs, these similarities demonstrate the generalizability of optimisation approaches to improve AED placement and accessibility. Reference: . Sun CLF, Demirtas D, Brooks SC, Morrison LJ, Chan TCY. Optimising public defibrillator deployment to overcome spatial and temporal accessibility barriers. Journal of the American College of Cardiology2016. Conflict of interest: None Funding: This work was funded by the ZOLL Foundation (ZOLL Foundation Research Grant) and supported by the Danish foundation TrygFonden with no commercial interest in the field of cardiac arrest.